WEB-BASED COMMUNITY ORGANIZATION REGISTRATION APPLICATION - Muhammad Rian Almadani; Muhammad Khoiruddin Harahap (Institute of Computer Science (IOCS), 2022)
The National Unity and Political Body, which is the Social and Political Directorate of North Sumatra Province, was merged with the Civil Defense Regional Headquarters of North Sumatra Province (MAWIL HANSIP PROVSU) to become the National Unity and Community Protection Agency of North Sumatra Province (BAKESBANG LINMAS PROVSU) in accordance with North Sumatra Provincial Regulation Number 4 2001 concerning Organization and Work Procedures of Regional Technical Institutions of North Sumatra Province and North Sumatra Governor's Decree Number: 061.1.436.K/Year 2002 concerning Duties, Functions and Work Procedures of the National Unity and Community Protection Agency of North Sumatra Province. Information cannot be separated from the various conflicts that occur in the surrounding community. Registration is the recording of things or identities such as names, addresses and so on in an educational institution, registration is a very important matter. data. The purpose of this research is to produce an information system for Reporting and Registration of Ormas at KESBANGPOL. This study uses the Waterfall method, where user needs are the main point in making the system. The result of this research is an information system that can facilitate the reporting and data collection system that is currently running at KESBANGPOL and minimizes the risks that will occur